Procedimientos de Eutanasia Humanitaria de Ganado Enfermo, Herido y/o Debilitado, Tarjeta de Referencia Eutanasia en Ganado Bovino - Jan K. Shearer; Paul Nicoletti; Pedro Melendez (EDIS)
VM-158, a full-color desk card by Jan K. Shearer, Paul Nicoletti and Pedro Melendez, is the Spanish language version of VM-154, "Humane Euthanasia Procedures for Sick, Injured, and/or Debilitated Livestock, Desk Card on Euthanasia of Cattle." It describes the correct way to humanely euthanize cattle using gunshot or penetrating captive bolt. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, April 2007.